Review on the application of imaging examination for brain injury in premature infants - Zhang, Qing; Zhou, Xihui (Frontiers in Neurology, 2023)
Brain injury is the main factor leading to the decline of the quality of life in premature infants. The clinical manifestations of such diseases are often diverse and complex, lacking obvious neurological symptoms and signs, and the disease progresses rapidly. Due to missed diagnosis, it is easy to miss the best treatment opportunity. Brain ultrasound, computed tomography (CT), magnetic resonance imaging (MRI), and other imaging methods can help clinicians diagnose and assess the type and extent of brain injury in premature infants to some extent, but the three methods have their own characteristics. This article briefly reviews the diagnostic value of these three methods for brain injury in premature infants.